1998
DOI: 10.1002/clc.4960211204
|View full text |Cite
|
Sign up to set email alerts
|

Salutary effects of aspirin in coronary artery disease are not limited to its platelet inhibitory effects

Abstract: Summary:Aspirin is widely used in the treatment and prevention of coronary artery disease (CAD). However, other platelet inhibitory agents, which inhibit platelet activation, have not been found to be effective or as effective as aspirin. The discrepancy between the efficacy of these compounds and aspirin suggests that the therapeutic efficacy of aspirin may not be limited to its platelet inhibitory effect. In this review, the basis for a unique place for aspirin in the therapy of patients with CAD is discusse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…Aspirin is believed to be effective primarily by inhibiting platelet aggregation, but inhibition of inflammation [8], smooth muscle cell proliferation [9] and oxidative process [10,11] also contribute to aspirin's effects. Stimulation of apoptosis [12] and NO synthesis [13,14] by aspirin may also relate to its overall salutary effect.…”
Section: Introductionmentioning
confidence: 99%
“…Aspirin is believed to be effective primarily by inhibiting platelet aggregation, but inhibition of inflammation [8], smooth muscle cell proliferation [9] and oxidative process [10,11] also contribute to aspirin's effects. Stimulation of apoptosis [12] and NO synthesis [13,14] by aspirin may also relate to its overall salutary effect.…”
Section: Introductionmentioning
confidence: 99%
“…Given the prominent scarring and early atherosclerosis reported in patients with systemic vasculitis with long-term survival, maintenance with antiplatelet agents would appear to be useful, although long-term studies have not been conducted. We recommend daily aspirin for patients after treatment of isolated angiitis as well as for a variety of disorders involving vasculitis of the peripheral nervous system [40]. Aspirin is indicated for thrombosis prophylaxis.…”
Section: Antiplatelet Agentsmentioning
confidence: 99%
“…It is a cornerstone of therapy in acute coronary syndromes and has been shown to reduce atherosclerosis-related events in a multitude of clinical studies [97,98]. Kharbanda et al have reported a protective effect of aspirin against endothelial dysfunction [99].…”
Section: Antiplatelet Therapy: Aspirinmentioning
confidence: 99%